Geometry with a STEM and Gamification Approach: A Didactic Experience in Secondary Education - Moral-Sánchez, Silvia Natividad (IOAP-MPDI, 2022)
Recent societal changes have meant that education has had to adapt to digital natives of the 21st century. These changes have required a transformation in the current educational paradigm, where active methodologies and ICT have become vehicles for achieving this goal, designing complete teaching sequences with STEM approaches that help students to learn. Under a gamified approach, this document addresses a didactic proposal in geometry focused on STEM disciplines. This proposal combines tools such as AR, VR, manipulative materials, and social networks, with techniques such as m-learning, cooperative-learning, and flipped-learning, which make methodological transformation possible. The research was carried out during two academic years under an action research framework. It departed from a traditional methodology and, in two cycles, methodology was improved with the benefits that gamification brings to STEM proposals in Secondary Education. The data gathered in the experiment were analysed following a mixed method. Learning produced, strategies employed, successes and errors, and results of a questionnaire are presented. Evidence shows an improvement in academic performance from 50% fails to 100% pass, most of the students ended up motivated, participation was of the whole group, more than 80% showed positive emotions, and thanks to the cooperative-learning, group cohesion was improved.
Keywords: Geometría; Geometry education; STEM; Gamification; ICT; Action research; Virtual reality; Augmented reality; Breakout EDU; Motivation